The Arts as Means of Socialization in Alison Bechdel's Fun Home - Daniel Dyonisius (Undergraduate Research Journal for the Human Sciences, 2016)
Alison Bechdel’s Fun Home suggests that socialization through the arts, such as writing and drawing, involves a constantly changing interpretation of reality that can contribute to a process of self-identification. The arts provide a foundation for Alison to make a connection to her family, yet also to detach from her parents’ influences at the same time. Emphasizing a social aspect of this process, her self-identification not only involves a reflection of her own life but also integrates her ability to navigate environments filled with the arts and others’ influences in shaping her personality. As an artist, Bechdel incorporates words and pictures to repair her relationship with her father and conveys a story of how she persistently constructs her identity. Nonetheless, her work as a whole reflects a broader significance for society: the creation of self-identity is not a linear process, but rather involves points of continuity and discontinuity that are shaped by the context in which one grows up. At the same time, such context is influenced by interactions between one’s self and agents of socialization mediated through important and specific means, such as the arts.
Keywords: Socialization; arts; fun; home